2004
DOI: 10.1016/j.femsle.2004.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Non-exhaustive extraction techniques (NEETs) for the prediction of naphthalene mineralisation in soil

Abstract: Non-exhaustive extraction techniques (NEETs) have been shown to measure the putatively bioavailable fraction of hydrophobic compounds in soil. To date, these studies have only considered bioavailability in a single soil type. In this study, naphthalene was amended into five different soil types and mineralisation, bacterial biosensor response and the number of indigenous microbial naphthalene degraders were determined. Two NEETs were used to extract the naphthalene from soil; hydroxypropyl-beta-cyclodextrin (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 19 publications
1
17
1
Order By: Relevance
“…The observation that bioreporter measurements of naphthalene concentrations are lower than concentrations derived by solvent extraction and chemical analysis are due to the fact that naphthalene is highly sorbed onto soil particles and thus it is not bioavailable to the bacteria for biotransformation [73]. In the mid-2000s a series of studies was performed that indicated biosensor performance can be improved using a non-exhaustive extraction technique (NEET) [73].…”
Section: Biosensing With P Fluorescens Hk44mentioning
confidence: 99%
See 2 more Smart Citations
“…The observation that bioreporter measurements of naphthalene concentrations are lower than concentrations derived by solvent extraction and chemical analysis are due to the fact that naphthalene is highly sorbed onto soil particles and thus it is not bioavailable to the bacteria for biotransformation [73]. In the mid-2000s a series of studies was performed that indicated biosensor performance can be improved using a non-exhaustive extraction technique (NEET) [73].…”
Section: Biosensing With P Fluorescens Hk44mentioning
confidence: 99%
“…In the mid-2000s a series of studies was performed that indicated biosensor performance can be improved using a non-exhaustive extraction technique (NEET) [73]. In addition, this approach allowed for a determination of biodegradation potential of a PAH contaminated soil sample [58,73,79,80]. The main criteria for NEET to be compatible with biosensors is that the solvent should be primarily aqueous or if the extract is in an organic solvent it must be dilutable in an aqueous solution [79].…”
Section: Biosensing With P Fluorescens Hk44mentioning
confidence: 99%
See 1 more Smart Citation
“…Tenax hydrophobic resins (Chrompack, Bergen op Zoom, The Netherlands) and cyclodextrins recently were proven to give a reliable estimation for the bioavailable fraction of contaminants [12,13]. Cyclodextrin extractions follow equilibrium kinetics, and these extractions were applied in several studies to estimate the bioavailable fraction of polycyclic aromatic hydrocarbons (PAHs) [18][19][20]. Cyclodextrin extractions follow equilibrium kinetics, and these extractions were applied in several studies to estimate the bioavailable fraction of polycyclic aromatic hydrocarbons (PAHs) [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Chemically, bioaccessibility can be tested by using so called non-exhaustive extraction techniques (NEETs). NEETs employ, for instance, Tenax or cyclodextrins to rapidly retrieve a compound fraction from the sample that is similar to the fraction metabolized by (micro-) organisms during a much longer incubation period [29,30]. For example, Dick et al added [ 14 C]-labeled phenanthrene or pyrene to soils, and showed that the total fraction of PAHs metabolized by bacteria in the soil during thirty days as derived from [ 14 C]-CO 2 evolution was almost the same as the PAH-amount extracted by hydroxypropyl-beta-cyclodextrin [30].…”
Section: Bioavailability and Bioaccessibility Assays With Mbsmentioning
confidence: 99%